Socioeconomic variations in hysterectomy: evidence from a linkage study of the Finnish hospital discharge register and population census. Issue 1 (February 1997) - Luoto, R; Keskimäki, I; Reunanen, A
Abstract : STUDY OBJECTIVE: To explore variations in rates for hysterectomy in relation to social class, education, and family income. DESIGN: Retrospective analysis of the 1988 Finnish hospital discharge register linked individually to the 1987 population census. SETTING: Finland. PARTICIPANTS: All women living in Finland aged 35 and over were the denominator population. The numerators were the 8663 women who underwent hysterectomy in 1988. MAIN RESULTS: The overall rate for hysterectomy was 63.5/10, 000 women aged 35 and over. There was a marked positive correlation between disposable family income and hysterectomy rates even after age, hospital catchment area, education, and occupational status were adjusted for. However, no linear trend for overall hysterectomy rates was observed in relation to social class or education. Procedures due to myomas, accounting for 48% of all hysterectomies, were more frequent among women of high socioeconomic status according to all socioeconomic indicators. Larger proportions of hysterectomies for myoma were also performed in patients in private hospitals and in pay beds in public hospitals than in women in worse off groups. CONCLUSIONS: Unlike the findings in earlier studies from other countries, there was a positive correlation between income and hysterectomy rates as a result of the high numbers of hysterectomies performed to treat myoma in the well off women. The findings are discussed in terms of socioeconomic differences in the use of private gynaecological services, and factors, such as parity and use of hormonal replacement therapy, that affect the growth of myomas.